2018
DOI: 10.1590/1807-01912018242405
|View full text |Cite
|
Sign up to set email alerts
|

Congruencia programática en el Cono Sur. Argentina, Chile y Uruguay en perspectiva comparada

Abstract: Los sistemas de partidos institucionalizados pueden convivir con una alta incongruencia programática entre élite y ciudadanía. Por el contrario, sistemas de partidos menos institucionalizados podrían estar en la posición de generar una mayor congruencia programática. Analizamos esta aparente anomalía en el Cono Sur de América Latina, comparando Argentina, Chile y Uruguay. Metodológicamente, utilizamos tres medidas de congruencia: promedios, comparación de distribuciones ( many to many ), distancia entre los vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Within political congruence studies, previous research has revealed a strong level of 'elite-mass policy congruence' in Argentina Warner 2017, Herrera andMorales 2018). Herrera and Morales (2018) found that, despite having a less institutionalized party system, Argentina has higher levels of programmatic congruence than Chile and Uruguay, in at least two of the policy dimensions that structure political competence.…”
Section: Why Argentine Parties' Supporters Can Be Programmatic Votersmentioning
confidence: 99%
See 2 more Smart Citations
“…Within political congruence studies, previous research has revealed a strong level of 'elite-mass policy congruence' in Argentina Warner 2017, Herrera andMorales 2018). Herrera and Morales (2018) found that, despite having a less institutionalized party system, Argentina has higher levels of programmatic congruence than Chile and Uruguay, in at least two of the policy dimensions that structure political competence.…”
Section: Why Argentine Parties' Supporters Can Be Programmatic Votersmentioning
confidence: 99%
“…Herrera and Morales (2018) found that, despite having a less institutionalized party system, Argentina has higher levels of programmatic congruence than Chile and Uruguay, in at least two of the policy dimensions that structure political competence. This could be explained by the fact that Argentina has a proportional electoral system which, from an institutional perspective, generates incentives for fragmentation and for searching for programmatic spaces by leaders and parties (Herrera & Morales 2018).…”
Section: Why Argentine Parties' Supporters Can Be Programmatic Votersmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple question has generated many academic debates in the last few years. The most recent studies carried out on the congruence between citizens and representatives have presented different patterns of ideological and programmatic congruence across countries or between parties and voters (Rodríguez 2017;Herrera and Morales 2018), largely due to the use of different methodological approaches (Lupu et al 2017). Nevertheless, the discussion on political congruence has been limited to the legislative power.…”
Section: Introductionmentioning
confidence: 99%